TATA KELOLA MENARA TELEKOMUNIKASI DI KOTA PEKANBARU - Cintika Effendi; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Telecommunications towers arragement in Pekanbaru still cause problems including the amount of towers than can affect the aesthetics in pekanbaru. Still the tower that has not pocketed a building permit erection of the tower location that is not in accordance with safety telecommunications towers arragement in Pekanbaru still cause problems including the amount of towers than can affect the aesthetics in pekanbaru. Still the tower that has not pocketed a building permit erection of the tower location that is not in accordance with safety and security and order The purpose of this study was to Knowing how Governance Telecommunication Tower in the city of Pekanbaru and the factors that impede arregement telecommunication towers.Researchers used the theory of George R. Terry in Manullang (2008: 3) which states that the principle of management that is no planning, organization, actuating and controling. This study used descriptive qualitative method, data collection through triangulation, namely: observation, interviews and documentation which the parties involved in this study as an informant. The outcome of reeaserch of this study indicate that Telecommunication Tower in Pekanbaru still didn’t meet the standart. this can be seen from the number of telecommunication towers unlicensed and placement that does not comply with the standards. Coordination and enforcement of sanctions that are not expressly so it does not give deterrent effect to the provider. so well that the management is not effective. Factor inhibiting arrangement Telecommunication Tower Pekanbaru is human resources, funding and infrastructure.Keywords : Arregement, telecommunication and tower